Outcome of Thyroid Surgery without Drainage Tube- A Study of 60 Cases (Journal of Armed Forces Medical College, Bangladesh, 2017)
Introduction: The use of a negative suction drainage tube in the neck in thyroid surgery is a common practice in order to avoid hematoma or seroma or other complication. It is associated with neck discomfort, post operative neck pain, delayed ambulation, longer hospital stay and ugly scar formation.Objective: To determine the advantages and safety of thyroid surgery without negative suction drainage tube.Materials and Methods: A cross-sectional observational study was carried out from September 2015 to May 2017 in the Department of Otolaryngology and Head-Neck Surgery, Kurmitola General Hospital, Dhaka Cantonment and Azmol and Life Aid General Hospital, Mirpur, Dhaka. A total of 60 patients who had undergone total thyroidectomy or hemithyroidectomy for thyroid disorders without drainage tube were included in this study. Patients with previous thyroid surgery, retrosternal goiter or malignant diseases of thyroid requiring neck dissection, undifferentiated thyroid cancer patients and those undergoing anticoagulant therapy were excluded from this study. Data were collected and recorded in a structured case report form. Data were processed and analyzed by the Statistical Package for Social Science (SPSS) version 20.Results: Hospital staying was shorter for 50 patients out of 60 and 83.34% patients were discharged on the 2nd postoperative day. The time of mobility of patient was shorter and 66.66% patients became ambulated from bed after 11-14 hours. Complication was less and only 11 patients developed different type of complications.Conclusion: Thyroid surgery can be done safely and perfectly without negative suction drainage tube in the neck with a shorter period of hospital stay, early ambulation, fewer complications and morbidities. However, the drain should be used in the presence of large dead space, particularly when there is a huge multinodular goiter or intrathoracic extension or when the patient is on anticoagulant or anti-platelet treatment.Journal of Armed Forces Medical College Bangladesh Vol.13(1) 2017: 62-65